Réalité des idéophones anglais (phonesthèmes) : propositions dans le cadre d’une approche de linguistique cognitive - Line ARGOUD (E-REA)
Drawing on key concepts of so-called ‘cognitive’ linguistics, I suggest that there exists a conceptual coherence within each of three heuristically constituted word classes (‘bl- / kn- / sk- words’). I claim that the semiological invariance displayed by these classes is the surface trace of a deep-level notional invariance, ultimately grounded on the conceptualisation of the body. This study could thus provide evidence of the reality of phonæsthemes, whose existence is a much debated issue among linguists.